An Investigation of Chronological Versus Cognitive Age Impact in the Kuwait Coffee Shop Market - Pleshko, Larry P.; Heiens, Richard A. (Organizations and Markets in Emerging Economies, 2015)
Given the growing body of research dedicated to self-perceived age and the cognitive age construct, it is widely believed that one’s self-perceived age may actually be a better predictor of age-related psychological states or attitudes than mere chronological age. Extending the research on cognitive age, the current study examines the impact of both cognitive age and traditional chronological age on the behaviors of coffee shop users in Kuwait. The study finds that chronological age and cognitive age are highly correlated, both in age levels and in terms of consumer behavior. Nevertheless, a large portion of the sample perceived themselves to be younger than their chronological age. This is especially true of consumers aged 55 and over. The main findings that differentiate chronological age from cognitive age are that as Kuwaiti consumers become chronologically older, coffee drinks become more important to them. Also, as cognitive age increases, consumers are less likely to drink coffee with friends.
Keywords: retailing; consumer psychology; emerging/transitional economies